Correlation of computed tomography with carotid plaque transcriptomes associates calcification with lesion-stabilization. (September 2019) - Karlöf, Eva; Seime, Till; Dias, Nuno; Lengquist, Mariette; Witasp, Anna; Almqvist, Håkan; Kronqvist, Malin; Gådin, Jesper R.; Odeberg, Jacob; Maegdefessel, Lars; Stenvinkel, Peter; Matic, Ljubica Perisic; et al.
Abstract: Background and aims: Unstable carotid atherosclerosis causes stroke, but methods to identify patients and lesions at risk are lacking. We recently found enrichment of genes associated with calcification in carotid plaques from asymptomatic patients. Here, we hypothesized that calcification represents a stabilising feature of plaques and investigated how macro-calcification, as estimated by computed tomography (CT), correlates with gene expression profiles in lesions. Methods: Plaque calcification was measured in pre-operative CT angiographies. Plaques were sorted into high- and low-calcified, profiled with microarrays, followed by bioinformatic analyses. Immunohistochemistry and qPCR were performed to evaluate the findings in plaques and arteries with medial calcification from chronic kidney disease patients. Results: Smooth muscle cell (SMC) markers were upregulated in high-calcified plaques and calcified plaques from symptomatic patients, whereas macrophage markers were downregulated. The most enriched processes in high-calcified plaques were related to SMCs and extracellular matrix (ECM) organization, while inflammation, lipid transport and chemokine signaling were repressed. These findings were confirmed in arteries with high medial calcification. Proteoglycan 4 ( PRG4 ) was identified as the most upregulated gene in association with plaque calcification and found in the ECM, SMA+ and CD68+/TRAP + cells. Conclusions: Macro-calcification in carotid lesions correlated with a transcriptional profile typical for stable plaques, with altered SMC phenotype and ECM composition and repressed inflammation. PRG4, previously not described in atherosclerosis, was enriched in the calcified ECM and localized to activated macrophages and smooth muscle-like cells. This study strengthens the notion that assessment of calcification may aid evaluation of plaque phenotype and stroke risk. Graphical abstract: Image 1 Highlights: Macro-calcification in carotid lesions was assessed by CTA and microarrays. Calcification was linked to a transcriptional profile typical for stable plaques. PRG4 was enriched in calcified ECM and localized to activated macrophages and SMCs. Assessment of calcification may aid evaluation of plaque phenotype and stroke risk.